Genome-wide identification and expression analysis of StTCP transcription factors of potato (Solanum tuberosum L.). (February 2019) - Wang, Yapeng; Zhang, Ning; Li, Ting; Yang, Jiangwei; Zhu, Xi; Fang, Chenxi; Li, Shigui; Si, Huaijun
Graphical abstract: The expression profiles of StTCP genes in different tissues. The StTCP genes transcript abundance were detected by RNA-Seq technology and expressed by FPKM values, and the color scale represents relative expression levels, red as higher expression levels and green as lower expression levels. Highlights: 31 TCP transcription factors were identified in potato. All StTCPs could take part in transcriptional regulation and had DNA binding ability. 7 StTCP genes were dramatically up-regulated during the release of tuber dormancy. Some StTCP genes obviously responded to different abiotic stresses and multiple hormones. Abstract: The plant-specific TCP transcription factors, which play critical roles in diverse aspects of biological processes, have been identified and analyzed in various plant species. However, no systematical study of TCP family genes in potato ( Solanum tuberosum L.) has been undertaken. In this study, a total of 31 non-redundant TCP transcription factors of potato were identified and divided into two subfamilies including three distinct subclades. The various orthologous TCP genes in Arabidopsis, rice, potato and tomato were identified using synteny and phylogenetic analysis. Protein motif analysis demonstrated that StTCPs in the same subclade shared similar conserved motif structures. Gene structure analysis showed that almost all StTCPs displayed highly conserved exon-intron organization. The analysis of StTCP gene promoter regions revealed that multiple cis -acting elements were involved in plant growth, development, hormone responses as well as stress responses. The result of StTCP gene expression profiles showed they had tissue-specific expression patterns which implied their differentiated functions. According to the results of quantitative RT-PCR (qRT-PCR), 7 StTCP genes were dramatically up-regulated during the release of tuber dormancy and some specific StTCP genes were strongly responding to different abiotic stresses and multiple hormones, which suggested they had important roles in potato growth and development processes. The results of our findings could provide comprehensive insights in StTCP family genes of potato for further functional investigations.